Investigation of antibody-based immune recognition of infections with Salmonella enterica serovars Typhimurium and Enteritidis - Naqid, Ibrahim (2016)
Salmonellosis causes significant economic losses to the pig and poultry industries. Pigs and chickens are also a significant source of Salmonella for humans, usually transmitted through the consumption of Salmonella contaminated chicken and pork products. Predominantly, Salmonella enterica serovar Typhimurium and Enteritidis remain a global health problem. Probiotics and prebiotics have been previously used as alternatives to antibiotic treatments in the protection against enteropathogens including S. Typhimurium. Here, we determined the effects of probiotic, prebiotic and synbiotic diets on humoral immune responses to oral S. Typhimurium challenge of pigs. The inclusion of probiotic Lactobacillus plantarum in the diet of piglets enhanced serum IgG, and IgM (p <0.001), and IgA (p <0.01) responses to S. Typhimurium infection. Similarly, inclusion of prebiotic lactulose in the diet increased serum levels of IgG and IgM (p <0.01) responses to pathogen, but not IgA levels. Inclusion of both feed additives as a synbiotic diet also significantly increased the level of IgG responses (p <0.05) to S. Typhimurium, but no differences were seen in the levels of IgM and IgA responses. However a signiﬁcant interaction of the pre and probiotics was observed when considering the immune responses to S. Typhimurium (IgM P=0.004; IgG and IgA, P<0.001 for interaction). These data support the use of L. plantarum or lactulose as strategies to contribute to the protection of weaned piglets from zoonotic bacterial pathogens, but caution must be taken when combining dietary supplements as combinations can interact. The mapping of antibody-based immune responses to Salmonella enterica infections for identifying epitopes/mimotopes has an important role in the development of both novel serological diagnostic assays and vaccines. Serological assays often underpin disease surveillance programs and are also required for the differentation of infected from vaccinated animals (DIVA) to allow the full implementation of vaccines alongside such surveillance. Here, panning of phage display peptide libraries coupled with Next Generation Sequencing was applied to the mapping of B-cell responses to Salmonella infections in both pigs and chickens. IgG from 12 pigs infected with S. Typhimurium were probed in parallel and compared to the equivalent IgG from the same pigs prior to infection. Seventy-seven peptide were enriched against IgG from multiple infected pigs, thirty-one peptides were synthesised and tested in ELISA and twelve peptides were highly discriminatory for pure IgG from infected pigs (P<0.05). Similarly, IgY from chickens infected with different Salmonella serovars were probed in order to identify mimotopes specific for S. Enteritidis infection. Twenty-nine peptides were enriched against IgY from multiple infected chickens, and then synthesised and tested in ELISA assays, tweleve of them were highly discriminatory for IgY following S. Enteritidis infections (p<0.05). The technology was also used to identify multiple peptides that were specifically bound by IgY from Salmonella infected chickens compared to a live attenuated vaccine and a killed vaccine. Twenty-five and thirty-six peptides for attenuated and inactivated vaccines, respectively, were identified as being specifically enriched in multiple infected chickens. Twenty and twenty-six of the most discriminatory peptides for live and killed vaccines, respectively, were applied in multi-peptide diagnostic assays that diagnosed infection with 100% sensitivity and specificity. The results demostrate that the identified peptides can be used to design serological DIVA tests with established inactivated and attenuated vaccines. Overall, the described next generation phage display (NGPD) technology repeatedly identified panels of epitopes/mimotopes recognised by multiple animals with a particular infection, providing an extremely efficient method to map host polyclonal antibody responses to S.Typhimurium and S. Enteritidis infections.